Strategy to provide Minimum Essential Force (MEF) in facing the current challenges of the global economy - Taufiqah taufiqah (Priviet Social Sciences Journal, 2026)
Indonesia’s archipelagic geography and exposure to Indo-Pacific tensions continue to underscore the need for credible defense capabilities. The Minimum Essential Force (MEF) program (2010–2024) concluded with realization of only approximately 65–70% overall (service-specific: Air Force ~51%, Army ~60%, Navy ~76% by 2023–2024 estimates), constrained by low defense spending (consistently 0.7–0.8% of GDP) and global economic pressures including supply-chain disruptions from U.S.–China competition. This qualitative policy analysis examines MEF optimization strategies—budget efficiency, technological modernization, domestic industry development, and international cooperation—while identifying persistent barriers. It addresses the post-2024 transition to Optimum Essential Force (OEF) under the Prabowo administration, filling contextual gaps by integrating recent fiscal trends (2025–2026 budgets) and policy shifts. Key contributions include updated evidence-based recommendations for resource optimization, reduced import dependency, and accelerated self-reliance, with implications for sovereignty, regional stability, and sustainable defense-industrial growth in archipelagic middle-income states.